Pemikiran Al-Ghazali Tentang Mekanisme Pasar Dan Penetapan Harga - Indra Hidayatullah (Universitas Islam Lamongan, 2020)
Market, country, individual and society have always been a hot topic of economic discussion. The market is one of the economic driver in a country that has an overall success can be seen from the market mechanism that carried out. The economic real good of the country is driven by market mechanisms that uphold freedom and justice. Hence, the market is free and impartial. The operation of a market will be determined by several factors such as price, demand and supply, distribution and specialization of workers. In case those factors run according to the rules in the country, the economy in the country will be stable certainly. The market is a natural mechanism for exchanging goods and services and it has been going on since the beginning of human changes. Islam places the market in an important position in the economy. The practices during the time of Rasulullah SAW and al-Khulafa> al-Ra>shidu>n showed a large market role. Rasulullah SAW really appreciated the price that was formed by the market as a fair price. In the history of economics world, several Islamic economies have emerged that raise scientific themes about market mechanisms, such as the thought of al-Ghazali. The book Ihya> ‘Ulu>m al-Di>n is one of his great works and one of the major works in the Islamic library. Although there are several other works of al-Ghazali in various fields of economics but the essence of his entire essay include his discussion of economics is the book Ihya> ‘Ulu>m al-Di>n. It provides features and characteristics of Islam in various sciences (moral, tasawwuf, economic and other), be one source of economics. Al-Ghazali, an Islamic scholar has socio-economics thought, rooted in a concept called “the socioeconomic welfare function”. The concept based of all his works is the concept of maslahah or social welfare, which is the concept that covers all human activities and makes close relations between individual and society. Keywords: al-Ghazali thinking, market mechanism, price determination